On divisor-closed submonoids and minimal distances in finitely generated monoids. (July 2019) - García-García, J.I.; Marín-Aragón, D.; Moreno-Frías, M.A.
Abstract: We study the lattice of divisor-closed submonoids of finitely generated cancellative commutative monoids. In case the monoid is an affine semigroup, we give a geometrical characterization of such submonoids in terms of its cone. Finally, we use our results to give an algorithm for computing Δ ⁎ ( H ), the set of minimal distances of H .